2019
DOI: 10.1037/spq0000292
|View full text |Cite
|
Sign up to set email alerts
|

Relations among academic achievement, self-esteem, and subjective well-being in school among elementary school students: A longitudinal mediation model.

Abstract: Situated within a positive psychology perspective, the current study examined the relations among academic achievement, self-esteem, and subjective well-being (SWB) in school among Chinese elementary school students using a longitudinal mediation model. A total of 807 elementary school students (Mage = 9.43 years; 52.9% male) completed a multimeasure questionnaire that tapped the targeted variables at 3 time points, across 18 months. After controlling for gender, age, and family socioeconomic status, the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 81 publications
(100 reference statements)
5
85
1
11
Order By: Relevance
“…The results of this study showed that students' self-esteem had both direct and indirect effects (through general health) on their academic performance, with direct effects being stronger. In line with this result, numerous studies have shown that higher levels of self-esteem are associated with better academic achievements [33][34][35][36] and affect self-esteem and depression symptoms [37], indicating the mediating role of general health in this relation. Some studies have found no association between selfesteem and academic performance or have found them to be negatively correlated [38,39].…”
Section: Discussionsupporting
confidence: 57%
“…The results of this study showed that students' self-esteem had both direct and indirect effects (through general health) on their academic performance, with direct effects being stronger. In line with this result, numerous studies have shown that higher levels of self-esteem are associated with better academic achievements [33][34][35][36] and affect self-esteem and depression symptoms [37], indicating the mediating role of general health in this relation. Some studies have found no association between selfesteem and academic performance or have found them to be negatively correlated [38,39].…”
Section: Discussionsupporting
confidence: 57%
“…A few studies considered subjective well-being and school achievement, indicating positive associations between the two variables, mostly through cross-sectional designs [27][28][29]. Similar associations were identified also through some longitudinal studies [5,13,[30][31][32].…”
Section: School-related Well-being and Educational Outcomesmentioning
confidence: 70%
“…Our finding is consistent with previous study findings that (a) self‐esteem has a long‐term effect on itself (Marshall et al., 2014), (b) family support also positively affects family support over subsequent years (Duineveld et al., 2017), and (c) life satisfaction at wave two shows the same result, predicting positive life satisfaction over two subsequent waves (cf. Yang et al., 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Orth, Robins, and Widaman (2012) found in their 12‐year study of 1,824 individuals via cross‐lagged regression analyses that self‐esteem was the cause, rather than the consequence, of life outcomes such as relationship satisfaction and that this finding was consistent through four generations. Meanwhile, Yang, Tian, and Huebner (2019) reported a mediational role of self‐esteem in the relationship between academic achievement and subjective well‐being in school among Chinese students.…”
Section: Literature Reviewmentioning
confidence: 99%